Pemberdayaan Pendidikan dan Keagamaan Anak Berbasis Participatory Action Research pada Masyarakat Desa Biring Kassi Kabupaten Takalar: Empowerment of Children's Education and Religion Based on Participatory Action Research in the Community of Biring Kassi Village, Takalar District - Muhammad Taufan Djafri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This community service program aimed to enhance the quality of education and religious development within the community through formal and non-formal educational activities focused on strengthening Islamic character, improving Qur’anic literacy, and introducing basic Arabic language skills. The program was implemented in Biring Kassi Village, North Galesong District, Takalar Regency, Indonesia, using a Participatory Action Research (PAR) approach that positioned the community as both a partner and the primary stakeholder throughout the planning, implementation, evaluation, and sustainability phases of the program. The implemented activities included General Learning Assistance at SDN 87 Tamanroya, an Islamic Short Course (Pesantren Kilat), Basic Arabic Language Instruction, and Qur’anic Learning Programs at TK/TPA (Qur’anic learning centers for children). The findings indicate that these programs successfully enhanced students’ learning motivation, strengthened their foundational understanding of Islamic teachings, improved their Qur’anic reading skills and memorization of daily supplications, and fostered greater interest in Arabic as the language of the Qur’an. Furthermore, the program contributed to strengthening collaboration among educational institutions, the local community, and higher education institutions in supporting youth development. The implementation of the PAR approach combined with SOAR analysis proved effective in designing community-based programs that addressed local needs and increased community participation in educational and religious activities. Despite challenges related to the limited duration of program implementation and the diverse characteristics of participants, the program demonstrates that integrating general education, Islamic education, and Arabic language learning through a participatory community-based approach has significant potential to support human resource development and strengthen the socio-religious life of rural communities in a sustainable manner.